20 ans de transparence à Genève - Cottier, Bertil (sui generis Verlag, 2022)
A few years before Confederation, the canton of Geneva adopted a law on transparency, the objective of which is to promote the free formation of opinion and participation in public life. LIPAD celebrated its 20th anniversary on March 1, 2022. On the occasion of this anniversary, this book reviews the history of the legal text and its application by the mediator, then the cantonal official. The other contributions relate to the use of the law by journalists, the relationship with the principle of good faith, the protection of private interests, access to public archives, access to school examinations, the principles of procedure , the Friborg example and the future of transparency.